Le rôle du jeu numérique dans l’enseignement/apprentissage du français pour les enfants (PRECOCE) - مرعي ليليان (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The development of the role of Games in the field of teaching/learning French language in general has led to an effective utilization of games in learning and teaching French to young learners. The beginning was with traditional games, then video games and recently there is the utilization of electronic games or what is called the social games. This development was the result of the development of technology and its nature throughout the last decade. There are several studies that show the disadvantages of using electronic games in language classes. However, there are studies that emphasize the important role that these games can play in classes of French young learner.